2022
DOI: 10.1111/mec.16583
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of preovipositional embryonic arrest in a nonsquamate reptile (Chelonia mydas)

Abstract: After gastrulation, oviductal hypoxia maintains turtle embryos in an arrested state prior to oviposition. Subsequent exposure to atmospheric oxygen upon oviposition initiates recommencement of embryonic development. Arrest can be artificially extended for several days after oviposition by incubation of the egg under hypoxic conditions, with development recommencing in an apparently normal fashion after subsequent exposure to normoxia. To examine the transcriptomic events associated with embryonic arrest in gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
(122 reference statements)
1
4
0
Order By: Relevance
“…Rather, they appear to be progressively modulated by oxygen availability, so that embryonic development is directly dependent on the ambient oxygen concentration. This conclusion agrees with Gárriz et al's [27] report of differences in transcriptional activity between fresh-laid embryos, embryos incubated in normoxia and embryos in hypoxia-extended arrest. They found that embryos in all three groups were transcriptionally distinct.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Rather, they appear to be progressively modulated by oxygen availability, so that embryonic development is directly dependent on the ambient oxygen concentration. This conclusion agrees with Gárriz et al's [27] report of differences in transcriptional activity between fresh-laid embryos, embryos incubated in normoxia and embryos in hypoxia-extended arrest. They found that embryos in all three groups were transcriptionally distinct.…”
Section: Discussionsupporting
confidence: 93%
“…Oxygen-sensing pathways dependent on hypoxia-inducible factors have been identified as potentially important mediators of hypoxia-induced embryonic arrest in zebra fish [ 53 ] and green sea turtles [ 27 ]. Our current findings indicate that these mechanisms do not operate as a simple ‘ switch’, either permitting or blocking embryonic development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of other turtle species have shown that embryos pause development at the gastrula stage and the arrest is maintained by hypoxia (~1% O 2 in the oviducts) (Kennett et al, 1993; Rafferty et al, 2013; Rings et al, 2015; Williamson et al, 2017). Embryos regulate gene expression in response to oxygen availability (Gárriz et al, 2022) and increases in oxygen availability when the eggs are oviposited break the embryonic arrest, even with small increments in %O 2 (Adams et al, 2022; Rafferty et al, 2013). Conversely, artificially maintaining eggs in extreme hypoxia after oviposition maintains the arrest and protects embryos from movement‐induced mortality (Williamson, Evans, Robinson, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%